(untitled) (Research, Society and Development, 2025)
Objective: To analyze the effectiveness of beta-alanine supplementation in athletes undergoing strength and endurance training. Methodology: The study was conducted through a literature review, based on research published between 2015 and 2025 in Portuguese and English, including scientific articles and literature reviews addressing the topic, emphasizing the systemic effects of beta-alanine and its use by athletes in strength and endurance training. The databases used were PUBMED, EBSCO and SCIELO. Discussion: Supplementation proved relevant for both strength and endurance training,with more significant results in strength training,although it is also applicable in endurance training. The main function identified for beta-alanine was the synthesis of carnosine,which acts neutralizing the hydrogen ions during exercise,reducing the perception of effort. The main side effect reported was paresthesia. The effects of beta-alanine may vary according to the sport modality and target population. Final considerations: Beta-alanine is effective and applicable for both strength and endurance training due to its mechanism of action, being able to enhance performance across different types of training. However,the intensity of its effects may vary according to the sport and the athlete profile.